The Virtual Synchronous Zoom On and Zoom Off : Combined with Engaging Media toward EFL Learners' Vocabulary Development - sholihah, faizatus (Universitas Muhammadiyah Gresik, 2021)
Abstract Due to the popularity of online learning using zoom application which has been implemented by several educational circles in pandemic era, has showed several issues related to their virtual zoom learning. This study is aimed to investigate the efficiency of learning vocabulary using virtual synchronous zoom in collaboration with engaging media, by turning learners’ video on and off. Pre-test and post-test with the same item and form of multiple choice questions were given to two different groups of 30 participants with the same duration of time, media and topic to measure EFL learners’ vocabulary development using experimental design and was analyzed using several quantitative tests. 25 items of instruments used were tested based on their validity and reliability. Questionnaires of Thai and English language versions were filled in by EFL learners with the total of 10 items. The results showed that the 2 groups of EFL learners showed positive results in enhancing their vocabulary mastery, but the EFL learners’ group who turned their video on had higher results compared to those who turned their video off. In addition, the EFL learners of zoom on group also experienced less difficulty and inconvenience during the virtual learning process.